Pharmacologic inhibition of somatostatin receptor 2 to restore glucagon counterregulation in diabetes - Hoffman, Emily G.; D’Souza, Ninoschka C.; Liggins, Richard T.; Riddell, Michael C. (Frontiers in Pharmacology, 2024)
Glucose homeostasis is primarily maintained by pancreatic hormones, insulin and glucagon, with an emerging role for a third islet hormone, somatostatin, in regulating insulin and glucagon responses. Under healthy conditions, somatostatin secreted from pancreatic islet δ-cells inhibits both insulin and glucagon release through somatostatin receptor induced cAMP-mediated downregulation and paracrine inhibition of β- and α-cells, respectively. Since glucagon is the body's most important anti-hypoglycemic hormone, and because glucagon counterregulation to hypoglycemia is lost in diabetes, the study of somatostatin biology has led to new investigational medications now in development that may help to restore glucagon counterregulation in type 1 diabetes. This review highlights the normal regulatory role of pancreatic somatostatin signaling in healthy islet function and how the inhibition of somatostatin receptor signaling in pancreatic α-cells may restore normal glucagon counterregulation in diabetes mellitus.